Alpha- and Gamma-Tocopherol Modulates the Amyloidogenic Pathway of Amyloid Precursor Protein in an in vitro Model of Alzheimer’s Disease: A Transcriptional Study - Pahrudin Arrozi, Aslina; Shukri, Siti Nur Syazwani; Mohd Murshid, Nuraqila; Ahmad Shahzalli, Ahmad Baihaqi; Wan Ngah, Wan Zurinah; Ahmad Damanhuri, Hanafi; Makpol, Suzana (Frontiers in Cellular Neuroscience, 2022)
Alzheimer’s disease (AD) is a neurodegenerative disorder and the most common form of dementia. The neuropathology of AD is characterized by abnormal accumulation of insoluble interneuron protein aggregates known as amyloid plaques and intracellular neurofibrillary tangles in the brain, both ultimately leading to extensive neuronal degeneration. Antioxidants, such as tocopherols have been touted as a potential therapeutic agent to delay AD’s progression. Alpha-Tocopherol is the most biologically active form and widely studied compared to other isomers (beta-, gamma-, and delta-tocopherol). This study aimed to elucidate the modulatory role of tocopherol isomers on the expression of genes related to APP processing in Alzheimer’s disease cell models. Untransfected SH-SY5Y, SH-SY5Y-APP WT, SH-SY5Y-APP Swe and SH-SY5Y-APP Swe/Ind models were cultured and treated with tocopherol isomers (alpha-, beta-, gamma-, and delta-tocopherol) for 24 hours. AB-42 production and APP gene and protein expression were determined to screen for the most effective dosage of tocopherol isomers. Subsequently, quantitative one-step real-time PCR was used to determine the expression of genes related to APP processing. Reduction in APP gene expression was observed in untransfected control SH-SY5Y cells with alpha- and gamma-tocopherol treatment as compared to untreated group (p<0.05). Both alpha- and gamma-tocopherol significantly decreased APP gene expression at 100 and 80 uM dosages respectively in SH-SY5Y-APP-Swe as compared to the untreated group (p<0.05). However, no significant change was observed in both untransfected control and SH-SY5Y-APP-Swe cells with beta and delta-tocopherol treatment. AB-42 production decreased significantly in SH-SY5Y-APP-Swe treated with both dosages of alpha- and gamma-tocopherol (p<0.05) as compared to the untreated group while no significant change was observed in untransfected control SH-SY5Y cells. Determination of APP protein expression did not show any significant difference in both untransfected control and SH-SY5Y-APP-Swe cell treated with all isomers of tocopherol. However, alpha- and gamma-tocopherol were shown to reduce the expression of BACE1, APH1B and NCSTN, while increasing the expression of SIRT1. In conclusion, tocopherol isomers such as alpha- and gamma-tocopherol is a potential therapeutic agent to ameliorate the burden of Alzheimer’s disease by altering the expression of genes related to APP processing.